Universidade e empresa: uma análise das relações científicas e tecnológicas entre a Universidade Federal de Roraima e as empresas do estado de Roraima - Silva, Heloane do Socorro Sousa da (2015)
Considering the importance of universities as producers of knowledge, and companies like producers of technologies and the Government as an integrating agent of the relationships between these actors, the objective of this research was to analyze the scientific and technological relations between the Federal University of Roraima and Roraima companies under the bias of the Triple Helix theory developed by Henry Etzkowitz and Leot Leydesdorff and Model Cooperation Process University-Enterprise created by Bonaccorsi and Piccaluga. The research is explanatory and the methodology used was field research and literature. The approach’s character is qualiquantitative and the tabulation of the data received quantitative treatment to support the qualitative aspects described in the analysis of the collected data. As a result, the survey indicated that the relations established between the Federal University of Roraima and Roraima companies exist, but are still incipient to the process of innovation and the development of the state, requiring coordination between these actors and the promotion of effective and continuous policies sustained by the state government as an incentive to university-enterprise relationship.